PENGARUH SUASANA, PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI NIKU COFFEE PONDOK INDAH - Rehan Verka Ananda; Bonifasius MH Nainggolan (LPPM Universitas Asa Indonesia, 2023)
This study aims to find out how the atmosphere of Niku Coffee Pondok Indah, price perceptions, and product quality affect customer purchasing choices. This study uses a quantitative methodology. Participants in this study were customers of Niku Coffee Pondok Indah. An accidental sampling approach, which selects a sample by chance from the available sample units, is used to collect the research sample. In this study, a total of 183 individuals were used as respondents. Because the dependent variable is more than one, the data is collected by distributing questionnaires, and data analysis uses multiple linear regression techniques. The findings from this study indicate that the atmosphere, perceived price, and product quality partially or simultaneously affect the purchase choice at Niku Coffee Pondok Indah.